A case report of hepatic angiomyolipoma, inflammatory subtype. Clinico-pathological characterization: a diagnostic challenge - Francisco Javier Velasco-Albendea; María Jesús Gil-Belmonte; Beatriz Estébanez-Ferrero; Orlando Fuentes-Porcel; Bruno José Nievas-Soriano (BMC, 2023)
Abstract Background Angiomyolipoma is a benign mesenchymal neoplasm of a wide histological heterogeneity belonging to the PEComa "family." The liver, after the kidney, is their second most frequent location. However, inflammatory hepatic AMLs constitute a rare entity, with only fourteen documented cases until 2020. These neoplasms can overlap morphological features of IgG4-related diseases, being of great diagnostic relevance to demonstrating myomelanocytic-lineage differentiation of the neoplastic cells. Case presentation: we present a new case of an inflammatory hepatic AML resembling an IgG4-related disease in a 35-year-old woman with a subcapsular 5 cm mass confined to segment VII of the right hepatic lobe. Although having reduced its size along the tumor's natural evolution, complete tumor resection was decided due to its hypermetabolic behavior (max. SUV = 12,6) assessed by PET-CT scan. Finally, the patient underwent a right hepatectomy due to spontaneous rupture and bleeding of the lesion during the intervention. All the diagnostic and therapeutic procedures occurred in the last months of the COVID-19 pandemic. Conclusions: This review aims to describe inflammatory hepatic AML histological and immunohistochemical features. We further sought to establish a clinicopathological contextualization of this tumoral subtype.